Моделі та методи розподілу мережевого ресурсу комп'ютерних мереж геоінформаційной системи екологічного моніторингу - Нааем, Хазім Рахім Нааем (НТУ "ХПІ", 2018)
Дисертація на здобуття наукового ступеня кандидата технічних наук за спеціальністю 05.13.05 – Комп'ютерні системи та компоненти. – Національний технічний університет "Харківський політехнічний інститут", Харків 2018. Дисертаційна робота присвячена вирішенню науково-практичної задачі удосконалення методу розподілу мережевого ресурсу комп'ютерних систем геоінформаційної системи екологічного моніторингу, що дозволяє підвищити оперативність функціонування цієї систем за рахунок використання розроблених моделей та методів розподілу обчислювального ресурсу мережі. Розроблено метод ухвалення рішень по організації стаціонарних постів системи ГІС екологічного моніторингу, який у відмінності від існуючих враховує параметр, що визначає швидкість зміни рівня поточного забруднення, величину концентрації небезпечних хімічних речовин (ОХВ) і розу вітрів, характерну для цієї місцевості. Запропоновано модель трафіку передачі даних гібридної комп'ютерної мережі ГІС екологічного моніторингу, яка враховує злиття інформаційних потоків, що мають різні статистичні моделі та метод розподілу мережевого ресурсу гібридної комп'ютерної мережі ГІС за рахунок використання технології MIMO, що дозволяє на 12-15% понизити час, необхідне на доставку даних моніторингу. Розроблена модель програмно-апаратних засобів, використання якої враховує особливості безпровідній передачі даних від декількох джерел інформації у гібридної комп'ютерної мережі ГІС.

Thesis for scientific degree candidate of technical sciences in the specialty 05.13.05 – computer systems and components. – National Technical University "Kharkіv Polytechnic Institute", Kharkіv 2018. The dissertation is devoted to the solution of the scientific and practical task of improving the method of network resource distribution of computer system of the geographic information system for ecological monitoring, which allows increasing the efficiency of functioning of these systems by using already developed models and methods of computing resource distribution of the network. The structure of GIS for environmental monitoring is developed, its main sub-systems and interaction principles are defined. The structure of hybrid computer network for digital data transmissions proposed, which allows optimizing the process of data transmission for environmental monitoring. The method of making decisions on the foundation of stationary posts of GIS for environmental monitoring is provided, which, in contrast to the existing ones, takes into account the parameter that determines the alteration rate of the then-current pollution level, the magnitude of the concentration of hazardous chemicals (HAZCHEM), and the wind rose specific for the area in question. Also, this method takes into consideration that the difference of HAZCHEM concentration in space varies from point to point. The whole from the abovementioned allows localizing zones of potential pollution and severely reducing the number of specialized observation posts (by 10-15%). The data transmission traffic model is developed for the hybrid computer network (CN) of the environmental monitoring GIS. This model takes into account the merging of information flows, which have different statistical models. The use of the offered model allows shortening the computer network data transmission rate by 13%. The network resources distribution method for the hybrid computer network of the environmental monitoring GIS is developed through the use of MIMO technology, which allows reducing the time required for monitoring data delivery by 12-15%. The model of hardware and software has been developed, the usage of which considers the features of wireless data transmission from several information sources in the hybrid computer network of GIS, thereby allowing to reduce the package loss ratio and to increase the speed of data transmission for the hybrid CN of GIS. The offered efficiency enhancement models and methods in computer networks of GIS have been examined in simulation modeling and experimental studies, which have thereby confirmed the veracity and significance of the derived results. The developed software and hardware model for ecological monitoring GIS allows reducing dates of receipt, processing and analysis of the ecological data, improving veracity and quality of the received results, and ensuring information safety.
Models and methods of network resource distribution of computer networks of the geoinformation system for ecological monitoring
Keywords: геоінформаційна система екологічного моніторінгу; бездротові мережі передачі інформації; метод розподілу мережевого ресурсу; стаціонарні пости; контроль екологічного моніторингу; автореферат дисертації; geoinformation system of ecological monitoring; wireless networks of information transmission; method of network resource distribution; stationary control posts for environmental monitoring; 504.064.36:[556:621.039]